Current Energy and Energy-Related Services Negotiations Viewed from Developing Countries Legal Protection - Hutajulu, Jonson (UI Scholars Hub, 2024)
This article aims to critically analyze current issues on energy services and energy-related services negotiation, viewed from developing countries legal protection on areas of energy production, transformation, transportation, distribution and sale of energy under the General Agreement on Trade in Services (GATS). Unfortunately, energy as an object of negotiation has been firmly agreed as goods, while markets on the aforementioned aspects reveal capacity gaps between developed and developing countries in order to reach efficient and fair energy services trade. Series of negotiations have been conducted creating scheduled of commitments among state parties interpreting GATS’ rules on affirmation enjoyed by developing countries to be more open and capable. The analysis in this paper is mainly construed using the economic analysis of international law stipulated by Thomas, Trachtman, Posner, and Djiwandono. It provides a framework of analysis on how negotiation under the WTO GATS generate a distinctive legal feature on international trade, and why developing countries need to be affirmed for entering their market access and exemption for the most favour nation clauses. This article reveals that current negotiation is still slow to omit inefficiency and monopoly, due to unclear definition and classification of these sectors. Factually, scheduled of commitments have pointed to test in terms of increasing developing countries’ understanding, allocation of all available resources and reducing potential risks when they give their commitments gradually and step by step approach. At the same time, developed countries also take measures on underlying necessity of legitimate reasons, authority, as well as their advanced resources to be shared to reduce capacity gaps for better market access to developing countries. As a result, proportionality, factuality, and non-discrimination underline issues to reach efficient and accountable energy and energy-related negotiation.